Efferent-mediated control of basilar membrane motion - Cooper, N P (Blackwell Science Inc, 2006)
Medial olivocochlear efferent (MOCE) neurones innervate the outer hair cells (OHCs) of the mammalian cochlea, and convey signals that are capable of controlling the sensitivity of the peripheral auditory system in a frequency-specific manner. Recent methodological developments have allowed the effects of the MOCE system to be observed in vivo at the level of the basilar membrane (BM). These observations have confirmed earlier theories that at least some of the MOCE's effects are mediated via the cochlea's mechanics, with the OHCs acting as the mechanical effectors. However, the new observations have also provided some unexpected twists: apparently, the MOCEs can enhance the BM's responses to some sounds while inhibiting its responses to others, and they can alter the BM's response to a single sound using at least two separate mechanisms. Such observations put new constraints on the way in which the cochlea's mechanics, and the OHCs in particular, are thought to operate.